Hubungan Iklim Pelayanan dengan Kualitas Pelayanan pada Perawat Unit Rawat Jalan RS Pemerintah X - Jupitawati, Ratna; Sulastiana, Marina; Yanuarti, Nurul (Al-Qalb : Jurnal Psikologi Islam, 2021)
The purpose of this study was to determine the relationship between service climate and service quality for nurses in the Outpatient Unit of Government Hospital "X". The method used is a quantitative method. The population in this study were 110 nurses in the Outpatient Unit of the Government Hospital "X", so the number of samples taken was 42 nurses who were carried out by random sampling technique. Analysis of the data used is descriptive analysis and correlational analysis using Pearson correlation. The results showed that there was a strong and significant positive relationship between service climate and service quality, meaning that the better the nurse's perception of the service, the better the service quality shown to patient nurses. This can be seen from the nurse's perception of the service climate that tends to be favorable and the assessment of the quality of their service which tends to be good.